Words of advice: Exposure to website model pictures and online persuasive messages affects the linguistic content and style of Women's weight-related social support messages. (October 2016) - Peña, Jorge; Pan, Wenjing
Abstract: This study examined how exposure to thin/obese and attractive/unattractive model pictures in websites affected language use when responding to weight loss or body acceptance posts. Participants exposed to attractive models were less socially oriented as indicated by using fewer function words and pronouns. These participants also used fewer discrepancy words (e.g., could, would), which may reflect upward social comparisons and activation of physical attractiveness stereotypes. Additionally, participants exposed to obese and unattractive models used more pronouns and perception words (e.g., weight, thin), implying downward social comparisons and priming of unhealthiness stereotypes that increased attention to other people's body shape. The findings show how words of advice are affected by situational cues including website images and persuasive posts. Highlights: Participants gave online advise after exposure to website photos and weight-related posts. Language use showed decreased social orientation after exposure to attractive models. Word choice revealed social comparisons and activation of stereotypes. Overall, words of advice are affected by website images and persuasive posts.